Meningkatkan Kemampuan Membaca Hijaiyah Berangkai Menggunakan Metode Al-Barqy bagi Siswa Autis Ringan di SMK Negeri 4 Padang - Viola Affelia Tamara; Damri Damri (Jurnal Penelitian Pendidikan Khusus, 2018)
The articles to load about a child have difficulty reading sequential hijaiyah letters and makhraj. The purpose of this research was aimed to improve the ability of mild autism student on reading about sequential Hijaiyah through Al-Barqy method. This type of research is experiment in the from of single subject research (SSR) by design A-B-A. The subject is a mild autism student. Data collection techniques are test, measure with percentage and data collection instrument in the from questions taken from sequential hijaiyah letters. The result of data analysis in condition and inter condition showed a positive improvement on read sequential hijaiyah letters. The research result then it is proven that al-barqy method can improve the ability to read sequential hijaiyah letters for a mild autism student. Suggestion for classroom teachers can use al-barqy method in practice and improve the ability to read sequential hijaiyah letters for a mild autism student.